2004
DOI: 10.1115/1.1833358
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Coupled Dynamic Response of a Mini Tension Leg Platform

Abstract: Role of mini tension leg platforms (TLP) in oil exploration and production in marginal deepwater fields is becoming increasingly important. Mini TLP combines the simplicity of a spar and favorable response features of a TLP. In this paper, the results of a detailed experimental and numerical investigation of the coupled dynamic behavior of a mini TLP are reported with special attention to hull-tether coupling. The experimental study has been carried out using a scaled model in wave flume with specially designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Most of them adopt numerical modelling and there have been a few studies comparing experimental and numerical modelling results (see, for example, Ormberg and Larsen 1998;Colby et al 2000;Ma et al 2000;Astrup et al 2001;Heuirtier et al 2001;Garrett et al 2002a;Garrett et al 2002b;Bhattacharyya et al 2003;Joseph et al 2004;Chen et al 2006;Low and Langley 2006;Yang et al 2012;Zhang et al 2008). Scaled model tests for deepwater systems inevitably have to be done in wave basins where water depth obviously cannot be scaled down.…”
Section: Example Simulations From Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Most of them adopt numerical modelling and there have been a few studies comparing experimental and numerical modelling results (see, for example, Ormberg and Larsen 1998;Colby et al 2000;Ma et al 2000;Astrup et al 2001;Heuirtier et al 2001;Garrett et al 2002a;Garrett et al 2002b;Bhattacharyya et al 2003;Joseph et al 2004;Chen et al 2006;Low and Langley 2006;Yang et al 2012;Zhang et al 2008). Scaled model tests for deepwater systems inevitably have to be done in wave basins where water depth obviously cannot be scaled down.…”
Section: Example Simulations From Literaturementioning
confidence: 98%
“…Bhattacharyya et al (2003) have observed that for deepwater TLPs, the tendon inertia is such that the low end of their frequency spectrum in bending may coincide with the high-frequency wave range, indicating that the dynamic modelling of the tendons is essential. As a follow-up, Joseph et al (2004) have resorted to distorted scale model of a mini-TLP, in which the tendons could be excited by waves in flume tests. Their experimental results agreed fairly well with the numerical results derived from an FE model.…”
Section: Example Simulations From Literaturementioning
confidence: 99%
“…Later, a distorted model of the tethers has been designed, and the experiments using such tethers revealed dynamic coupling of the floater and tether motions, and the results showed reasonably good comparison with numerical observations. 42,43 Model tests for deepwater structures are hampered by difficulties in modeling the water depth and to some extent the mooring/riser properties. In this context, a hybrid approach involving a combination of tests with truncated models and computer simulations with prototype characteristics is advocated.…”
Section: Coupled Analysismentioning
confidence: 99%
“…They considered only Morison wave loading. Joseph et al (2007) presented the design details of a 3-column mini TLP based on an existing 4-column mini TLP and carried out its numerical analysis with Morison equation alone for the wave force model Thus the importance of coupled analysis and combined wave force modelling is underscored in the literature. Several innovative designs and interesting geometrical configurations also are reported aiming towards savings and advantages in terms of material, time and cost, applicable to marginal deepwater sites.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya et al (2003) presented a detailed finite element methodology for the analysis of coupled dynamics of mini TLPs and the nature of hull-tether coupling and its physical modeling principles have been brought out. Joseph et al (2004) reported detailed experimental and numerical investigations on the coupled dynamic behaviour of a 4-column mini TLP with special attention to hull-tether coupling. Numerical investigation using several wave force models and validation with experiments identified the best suited wave force model, which is a combination of potential theory based wave loading on the hullcolumn entity and Morison-type wave loading on the slender cantilevering arms and tethers.…”
Section: Introductionmentioning
confidence: 99%